(untitled) (Research, Society and Development, 2023)
Since it was detected on December 31, 2019 in Wuhan in China, coronavirus typified as SARS-CoV-2 has been changing the course of history and being the subject of studies from various areas of knowledge today. Thus, this article is a narrative review, which aimed to analyze the scientific work on what possible impacts that the COVID-19 pandemic has caused child food practices in Brazil. The articles compiled in this study were selected through the databases: PubMed, Lilacs and Scielo. The survey was limited to articles published in the English and Portuguese languages, published in the last 3 years, using the standard descriptors: COVID-19; Pandemics; Eating behavior; Nutrition of the child and his correspondents in English, in all combinations the boolean and operator was used. It was observed that the children underwent several negative results from confinement in pandemic period, including changes in eating habits. Thus, this period has caused since the weight gain of this population, as well as the pandemic acted as a potentiate of social inequalities, with the growth of reports of food insecurity especially in the age group.